2021
DOI: 10.1249/mss.0000000000002829
|View full text |Cite
|
Sign up to set email alerts
|

The Motor Engram of Functional Connectivity Generated by Acute Whole-Body Dynamic Balance Training

Abstract: Purpose: Whole-body dynamic balance is necessary for both athletic activities and activities of daily living. This study aimed to investigate the effect of acute dynamic balance training on neural networks. Methods: We evaluated resting-state functional connectivity (rs-FC), white matter fiber density, fiber-bundle cross-section, and gray matter volume in 28 healthy young adults (14 women) before and after 30 min of slackline training using a randomized, counterbalanced crossover design. Results: The rs-FC bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…On an neural level, these demands may induce an additional stimulus to the brain compared with less complex exercise modes like RUN. This observation is supported by previous evidence reporting mode-specific modulations of RSN applying functional magnetic resonance imaging in the context of balance and coordination training (11,54). Therefore, exercise mode may be considered as a factor affecting exercise-induced modulations of brain networks.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…On an neural level, these demands may induce an additional stimulus to the brain compared with less complex exercise modes like RUN. This observation is supported by previous evidence reporting mode-specific modulations of RSN applying functional magnetic resonance imaging in the context of balance and coordination training (11,54). Therefore, exercise mode may be considered as a factor affecting exercise-induced modulations of brain networks.…”
Section: Discussionsupporting
confidence: 88%
“…Apart from intensity and volume, the mode of endurance exercise affects the physiological responses to exercise bouts because of differences in movement constraints, muscles involved, and muscle actions (8). Despite sports-specific factors such as involved limbs/ muscles, technique, and equipment that affect movement economy (9), endurance mode has been barely investigated as a factor modulating acute exercise-induced neuroplasticity of the resting brain (10,11). In contrast to exercise-intensity where metabolic processes affect brain signaling, endurance mode is likely to alter brain function because of task-specific activation of cortical areas involved into mode-specific sensorimotor control demands (12).…”
mentioning
confidence: 99%
“…In young individuals, two studies reported the effects of acute balance training on the performance of a non-trained static balance task. One of these studies reported a significant increase in unipedal stance time (+ 4%) but only while standing on an unstable balance disk and not while standing on a stable surface [ 56 ]. No reductions in the CoP velocity were reported following one day of balance training on an unstable device [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…One 30-min session of unipedal stance balance training on unstable boards decreased coherence between relevant muscle synergies and the left paracentral lobule synergy in the 40-Hz band (Piper rhythm) [ 74 ]. A 30-min session of heel-to-toe beam walking increased alpha power in the occipital and parietal areas and decreased power in the gamma band [ 75 ] and 30-min of slackline training increased resting-state functional connectivity between the left prefrontal cortex and the medial areas in the primary sensorimotor area [ 56 ]. Three consecutive days of treadmill slip perturbation training increased activity in several cortical regions (left middle frontal gyrus, right superior parietal lobule, right inferior occipital gyrus, and left lingual gyrus) during motor imagery of slipping and walking tasks [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation